Backyard poultry: contributions and opportunities for the peasant family - Hotúa-López, Laura Cristina (2021)
Introduction. The study of backyard poultry farming and the recognition and identification of its contributions, as well as their difficulties, allow fomenting its cultural, economic, and social value, for its promotion as an alternative of sustainable production. Objective. To analyze through literature review, backyard poultry farming as an expression of family agriculture, its contributions to food security, to women, to the family, to society, and to the genetic preservation of the species involved. Development. The Google Scholar® search engine was used and search formulas were applied that included key terms associated with the objective of the work, a tour was made through backyard poultry farming as a traditional productive practice, the importance of the knowledge acquired by the peasant communities was examined and their commercial opportunities were projected. Conclusion. Backyard poultry farming contributes to the balanced development of the territory and rural communities through the preservation of species, culture and tradition; its products have the potential for integration into specialized markets, as a result of sustainable family farming systems. However, their permanence in these markets is conditioned on overcoming production problems, hygienic and sanitary problems, related to the traditional poultry management.